Integrating sustainable practices in chili processing enterprises: A literature review - Hidayatullah, Anung Andi; Fatlianaa, Anggun Nindy; Umyati, Ani (Journal Industrial Servicess, 2024)
This study explores the integration of sustainability principles in Micro, Small, and Medium Enterprises (MSMEs), focusing on chili processing enterprises in Garut Regency. Using a systematic literature review, it analyzes 60 scholarly articles to provide a comprehensive overview of strategies for embedding economic, environmental, and social aspects into MSME operations. The findings emphasize the crucial role of clearly defined responsibilities and collaboration among various stakeholders, including business managers, government agencies, educational institutions, local farmers, and the broader community. The study highlights how these stakeholders can work together to foster a sustainable business environment that enhances profitability while promoting environmental conservation and social welfare. By offering a conceptual framework, this research addresses a significant gap in the literature on sustainable practices in the agricultural processing sector, providing practical insights and recommendations for MSMEs. This holistic approach ensures that these enterprises achieve long-term sustainability while meeting the economic, environmental, and social goals essential for their growth and competitiveness.